The Effect Of Addition Of Benzyl Amino Purine (BAP) and Bean Sprout Extract in Murashige and Skoog (MS) On The Growth Of Hybrid Cattleya Orchid Tissue Culture In Vitro - Elena Fitria Dewi; Ruly Budiono; Asep Zainal Muttaqin (Research Collaboration Community (RCC), 2026)
Cattleya orchids are highly sought-after ornamental plants, leading to the development of hybrid Cattleya orchids. However, conventional propagation of Cattleya orchids is considered difficult. Therefore, in vitro tissue culture is necessary as an alternative. Important factors in the success of tissue culture are the growing medium and plant growth regulators (PGRs), such as cytokinins and auxins. This study aimed to examine the effect of the addition of synthetic PGRs (BAP) and natural PGRs (bean sprout extracts) combined on the growth of hybrid Cattleya orchid tissue cultures in vitro. This study was conducted using a Completely Randomized Design experimental method with 5 levels of BAP concentration (0 ppm, 0.5 ppm, 1 ppm, 2 ppm, 3 ppm), bean sprout extract (0%, 5%, 7.5%, 10%, 12.5%) and a combination of BAP and bean sprout extract, namely control, BAP 0.5 ppm + 5% bean sprout extract, BAP 1 ppm + 7.5% bean sprout extract, BAP 2 ppm + 10% bean sprout extract, BAP 3 ppm + 12.5% ​​bean sprout extract on MS media. The parameters observed included plantlet height, number of leaves, number of roots, root length, and fresh weight. Data were analyzed using analysis of variance (ANOVA) and continued with Duncan's test. The results showed that the administration of BAP, bean sprout extract and their combination had a significant effect on the growth of plantlet height, number of leaves, number of roots, root length and fresh weight. The combination treatment of 2 ppm BAP and 10% bean sprout extract was effective in supporting the growth of hybrid Cattleya orchids.